A Smart Superhydrophobic Coating on AZ31B Magnesium Alloy with Self‐Healing Effect. Issue 14 (27th May 2016) - Zhang, Jialei; Gu, Changdong; Tong, Yueyu; Yan, Wei; Tu, Jiangping
Abstract : Superhydrophobic coatings with Cassie state can physically isolate the coating/substrate from the corrosive medium by virtue of their entrapped air‐pockets, thus providing corrosion protection. Self‐healing coatings are of interest for their ability in self‐repairing local damage caused by external factors. Such coatings with dual corrosion inhibiting function, i.e., superhydrohpobicity and self‐healing, are seldom produced. In this study, a novel chemical conversion coating (CCC) on the AZ31B magnesium alloy with dual function of superhydrophobicity and self‐healing is successfully fabricated from a Cr (III) containing deep eutectic solvent. The Cr(III) CCC is mainly composed of Cr2 O3 . Superhydrophobicity is achieved for the Cr(III) CCC by stearic acid modification due to its hierarchically microstructure. The smart Cr(III) CCC on the Mg alloy exhibits a great enhancement of corrosion resistance in the NaCl solution due to the proposed dual corrosion inhibiting function. The superhydrophobic effect of the coating provides the first corrosion barrier for the substrate. The second corrosion barrier can be stimulated when the superhydrophobicity is collapsed in the corrosion medium, i.e., the realization of self‐healing behavior of the coating. The formation of Cr‐based oxides or compounds caused by external factors is suggested as being responsible for the self‐healing mechanism of the smart coating. Abstract : A smart conversion coating on magnesium alloys with bi‐functional mechanism was fabricated from a deep eutectic solvent containing trivalent chromium. Superhydrophobicity of the coating provides the first corrosion barrier for the substrate. As superhydrophobicity is collapsed in corrosion medium, self‐healing of the coating works. Formation of Cr‐based oxides or compounds stimulated by external factors is responsible for the self‐healing mechanism.